THE DOCTRINE OF PRECEDENT IN SOUTH AFRICA - George Devenish (Obiter, 2022)
A certain degree of ambivalence and inconsistency is inherent in the nature and operation of the doctrine of precedent, which is an intrinsic part of our common law and in terms of the Constitution continues in force in our new jurisprudential dispensation. We have inherited it from English law and it continues to operate, although there is nothing in the Supreme Court Act to indicate explicitly that judges are bound to follow precedents. Nor is there anything expressly to this effect in the Constitution. This article endeavours to demonstrate, by examining the relevant case law, exactly how in the new dispensation, members of the judiciary observe the staredecisis rule. They do so because firstly, it has over the years, become customary to do so, and secondly, at present, it has certain important advantages for our jurisprudence.